2014
DOI: 10.1001/jamaophthalmol.2014.1761
|View full text |Cite
|
Sign up to set email alerts
|

Hourly Awakening vs Continuous Contact Lens Sensor Measurements of 24-Hour Intraocular Pressure

Abstract: IMPORTANCE All studies of 24-hour intraocular pressure (IOP) rhythm conducted to date have used repeated IOP measurements requiring nocturnal awakenings, potentially disturbing sleep macrostructure.OBJECTIVE To evaluate the effects on sleep architecture and IOP rhythm of hourly awakening vs a contact lens sensor (CLS) to continuously monitor IOP without awakening. DESIGN, SETTING, AND PARTICIPANTSCross-sectional study at a referral center of chronobiology among 12 young healthy volunteers, with a mean (SD) age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Although the sample size is small, these observations suggest that some artifacts on blood pressure may have occurred due to awakening subjects for the nocturnal IOP measurements. However, the impact may not significantly affect the estimation of 24-hour peak timing as reported previously in another study [36]. …”
Section: Discussionmentioning
confidence: 56%
“…Although the sample size is small, these observations suggest that some artifacts on blood pressure may have occurred due to awakening subjects for the nocturnal IOP measurements. However, the impact may not significantly affect the estimation of 24-hour peak timing as reported previously in another study [36]. …”
Section: Discussionmentioning
confidence: 56%
“…Obstructive sleep apnea syndrome and intraocular pressure fluctuations association [46]. Other studies, however, have reported a lower correlation between both values [47,48].…”
Section: Plos Onementioning
confidence: 79%
“…6 Since then, measurements of the IOP obtained using the CLS in patients with glaucoma, healthy subjects, and patients with sleep apnea syndrome have been reported. [7][8][9][10][11][12][13][14][15][16]18 However, there have been relatively a few reports about the influences of the CLS on the cornea. 13,[19][20][21] After wearing the CLS, the most common corneal/conjunctival finding is reported to be bulbar conjunctival hyperemia, followed by superficial punctate keratopathy and corneal epithelial erosion.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the previous studies were performed in participants with spherical power between −5 and 3 diopters (D) and cylindrical power 2D or less, [8][9][10][11][12][13] awareness of blurred vision is one of the main frequent adverse events with CLS. 8,10,[14][15][16] Although the CLS is available in three curvature radius sizes: steep, medium, and flat, 8 curvature radius size of CLS is selected based on the measured corneal curvature radius of the patient's eyes.…”
Section: Introductionmentioning
confidence: 99%